Implementation of Islamic Religious Education for Children with Special Needs in Elementary Schools - Wahyuningrum, Zulfa Indra; Mawardi, Imam; Usman, Nurodin (Prosiding University Research Colloquium, 2023)
Islamic Religious Education is more of an education contained in learning in public schools. It is the obligation of the school to provide religious lessons to students according to their beliefs. Whether it's intended for children with special needs or other normal children. Regular schools are a challenge for educators in providing learning rights for children with special needs at these schools. This study aims to find out how the implementation of Islamic religious education for children with special needs in regular schools is at SD Kartika XII-1. The method used by researchers is to use a qualitative approach. Data collection techniques by interviewing school principals, PAI teachers, and accompanying teachers or Shadow Teachers with ABK (children with special needs). The results of the study concluded that the implementation of Islamic learning for children with special needs begins with the steps for preparing PAI learning plans through identification, assessment or measurement, and compiling programs that are tailored to the needs of students with special needs.